Urban food forests in the American Southwest. Issue 1 (23rd August 2021) - Allen, James A; Mason, Andrew C
Abstract: Food forests are multilayered polycultures of mostly perennial species and an agroforestry practice well‐suited to the urban environment. They are gaining increasing attention in temperate regions of Europe and the United States, but, to date, there has been little research on them in the American Southwest. In this study, we visited 14 food forests, all but two of which were in urban or peri‐urban areas. At 12 of the food forests, we interviewed a person who established or manages them. The food forests span a significant range of the physical environments, types of communities, and ownerships found in the American Southwest. Despite challenges associated with the southwestern environment, such as the hot, dry climate and difficult soil conditions, we found clear evidence that food forests can be successfully established in the urban areas of this region. In addition to food production, these food forests are providing numerous other benefits such as mitigating the urban heat island effect, increasing local biodiversity, and improving the aesthetics of urban neighborhoods. While there is a need for additional research, a variety of networks and information sources have been established that are providing both practical information and inspiration for the establishment of additional food forests in the region. Core Ideas: Food forests occur in a range of environments and communities in the American Southwest. Despite the challenging climate and soils, food forests are a viable urban agroforestry practice. In addition to food, the food forests are providing other ecological and social benefits.